011 The relationship between tightness of the hip joint and shoulder/elbow injury in high school baseball pitchers – a prospective study. (3rd March 2020) - Hamano, Noritaka; Shitara, Hitoshi; Ichinose, Tsuyoshi; Sasaki, Tsuyoshi; Masataka, Kamiyama; Ryosuke, Miyamoto; Kurume, Fukui; Tajika, Tsuyoshi; Kuboi, Takuro; Endo, Fumitaka; Takagishi, Kenji; Chikuda, Hirotaka
Abstract : Background: The mechanics of pitching are quite complex, so improper coordination of the kinetic chain from the lower extremity to the trunk results in an improper upper arm position and increased risk of shoulder/elbow injury. Several studies reported that upper extremity tightness are risk factors for shoulder and elbow injuries in high school baseball players, however, studies on the relationship between tightness of the lower extremities and shoulder and elbow pain in pitchers have been insufficient. Purpose: The purpose of this study was to prospectively examine the relationships between hip ROM in the preseason and throwing-related shoulder/elbow injuries in the season in high school baseball pitchers. Design: Prospective cohort study Methods: The study included 125 high school baseball pitchers (median age 16.5 [15–17] years). The following physical parameters were assessed: (1) hip ROM (flexion, internal rotation [IR], external rotation [ER]) in the supine position, (2) hip ROM (IR, ER) in the prone position. After the season, the participants completed questionnaires regarding shoulder and/or elbow injuries, with injury defined as an inability to play for ≥1 week due to elbow/shoulder problems. The results of injured and non-injured patients were compared. Results: Eleven throwing-related injuries (9%) were observed during the season. In the injured group, the ROM of the plant side hip with 90° flexed external rotation was significantly lower than that in the non-injured group (40.0°±8.2° and 48.3°±11.7°, respectively; P=0.02). There was no significant difference in the ROM of the plant side hip with 0°flexed external rotation. No significant differences were observed between the injured and non-injured groups with respect to hip ROM on the trail side. Conclusion: A preseason decrease in the 90° flexed external rotation on the plant side was an independent risk factor for shoulder and elbow injuries in high school baseball pitchers.